COVID-19 and Employment in South Korea: Trends and Comparison with the 2008 Financial Crisis - Minhyuk Nam; Soohyung Lee (Institute of Labor Economics (IZA), 2021)
We examine the impact of COVID-19 on employment in South Korea as of June 2020. To estimate the causal effect, we use two complementary methods. First, using individual-level data without residence information, we estimate the effects by controlling for detailed characteristics of individuals. Second, using aggregate data without individual characteristics, we exploit the regional variation in the intensity of COVID-19 to measure the effects. We find that the COVID-19 pandemic decreased the employment rate by 0.82%p and increased the unemployment rate by 0.29%p. These estimated effects are 90%–140% larger than those of the 2008 Financial Crisis.
Keywords: E3; J2; J6; 330; COVID-19; financial crisis; unemployment; employment